Mohiniyattam - Deepti Omchery Bahlla (Invis Multimedia, 2003)
It is the dance of the Mohini, the classical enchantress of hindu mythology.Mohiniyattam is the female classical solo dance form of kerala.Noted for its wide swinging steps,mohiniyattam brings into one's mind of the graceful,gentle swaying of palm fronds.